Light-Cured Junction Formation and Broad-Band Imaging Application in Thermally Mismatched van der Waals Heterointerface - Cheng, Liyuan; Quan, Qinglin; Hu, Liang (Materials, 2024)
Van der Waals (vdW) heterostructures are mainly fabricated by a classic dry transfer procedure, but the interface quality is often subject to the vdW gap, residual strains, and defect species. The realization of interface fusion and repair holds significant implications for the modulation of multiple photoelectric conversion processes. In this work, we propose a thermally mismatched strategy to trigger broad-band and high-speed photodetection performance based on a type-I heterostructure composed of black phosphorus (BP) and FePS3 (FPS) nanoflakes. The BP acts as photothermal source to promote interface fusion when large optical power is adopted. The regulation of optical power enables the device from pyroelectric (PE) and/or alternating current photovoltaic (AC–PV) mode to a mixed photovoltaic (PV)/photothermoelectric (PTE)/PE mode. The fused heterostructure device presents an extended detection range (405~980 nm) for the FPS. The maximum responsivity and detectivity are 329.86 mA/W and 6.95 × 1010 Jones, respectively, and the corresponding external quantum efficiency (EQE) approaches ~100%. Thanks to these thermally-related photoelectric conversion mechanism, the response and decay time constants of device are as fast as 290 μs and 265 μs, respectively, superior to current all FPS-based photodetectors. The robust environmental durability also renders itself as a high-speed and broad-band imaging sensor.